Ketimpangan Gender di Layar Perak: Representasi Perempuan di Film Terlaris Indonesia - Maghfira Fitra Yuliantini (Umbara, 2021)
As part of popular culture, film is able to both reflect and shape the understanding and attitudes towards gender in a society. However, despite the increase of gender awareness in Indonesian society, there are still many filmmakers unfamiliar with gender issues. In fact, the unequal treatment and underrepresentation of female characters in film is a real issue within the Indonesian film industry. It is seen in the lack of films that positively representing women. Often, women are portrayed as being inferior to men. In addition, many films still sexually objectify women. This study attempts to analyze the depiction of women between highest-grossing films made by female directors and those directed by males. This paper aims to highlight how female participation within film production influences women’s representation in popular films. The data is analysed using the Bechdel test — a tool to measure representation of women in fictional stories. Furthermore, this study examines female attitudes, characters, and their roles within the film, as well as the ways in which other roles respond to female roles. This study finds that women are represented in greater proportion and are portrayed more positively in films directed by women. In conclusion, gender portrayal within film is greatly influenced by the actors behind the scenes.